The Specific Impact of Apolipoprotein E Epsilon 2 on Cognition and Brain Function in Cognitively Normal Elders and Mild Cognitive Impairment Patients - Gong, Liang; Xu, Ronghua; Liu, Duan; Lan, Lin; Zhang, Bei; Zhang, Chuantao (Frontiers in Aging Neuroscience, 2020)
Variants in the apolipoprotein E (APOE) gene play an important role in the development of Alzheimer’s disease (AD). Specifically, the APOE-ε4 allele is an established genetic risk factor for AD, while the APOE-ε2 allele is a protective factor against AD. However, the mechanism underlying this impact of APOE genotype on the pathogenesis of AD remain unclear. This study sought to investigate the influence of APOE genotype on cognition and neuroimaging features in cognitively normal (CN) elderly individuals and patients with mild cognitive impairment (MCI). A total of 177 participants were selected from the Alzheimer’s Disease Neuroimaging Initiative database, including 101 MCI patients and 76 CN individuals. A 2 × 3 (consisting of 2 groups and 3 APOE genotypes) analysis of covariance was carried out to measure the influences of diagnosis and APOE genotype on cognition and brain features, assessed based on global functional connectivity density (gFCD) and hippocampal volume. In addition, a mediation analysis was carried out to investigate the indirect influence of neuroimaging features on the relationship between APOE genotype and cognitive performance in the MCI group. This analysis revealed that APOE genotype had an influence on brain function in the bilateral precentral gyrus, right thalamus, and posterior cingulate cortex. In addition, an interactive influence between diagnosis and APOE genotype was found on general cognition, immediate memory, executive function, hippocampal volume, and gFCD in the right dorsolateral prefrontal cortex and medial prefrontal cortex. Finally, this mediation analysis revealed that hippocampal volume and gFCD in the thalamus may mediate the relationship between APOE genotype and cognitive performance in the MCI group. Taken together, our findings provide novel insights into the neural mechanisms underlying the genetically guided pathogenic mechanisms of AD.